A multi-level fuzzy comprehensive evaluation model to optimize biochar application schemes for potato cultivation in North China - Guo, Jiawei; Zhou, Hui; Jia, Liguo; Wang, Yongqiang; Fan, Mingshou; Wang, Meirong; Liu, Peng; Shang, Zhihui (Frontiers in Plant Science, 2025)
IntroductionThe North China region is a major potato production area, but water scarcity and poor soil fertility limit potato growth. Biochar is a promising approach to improve soil quality and enhance crop productivity. However, the effects of different biochar pyrolysis temperatures and application rates on potato growth, economic benefits, quality, water and fertilizer use efficiency, and soil nutrient retention remain unclear.MethodsA field experiment was conducted during 2023–2024 to evaluate the effects of biochar pyrolysis temperatures (T1: 300°C, T2: 500°C, T3: 700°C) and application rates (C1: 10 t ha−1, C2: 20 t ha−1, C3: 30 t ha−1) on comprehensive potato cultivation performance. A multi-level fuzzy comprehensive evaluation (PFCE) model was used to determine the optimal biochar application strategy.ResultsPotato growth indicators, water and fertilizer use efficiency, starch, and vitamin C content exhibited a parabolic trend, with the C2T2 treatment performing best. Net income was highest for the CK treatment in 2023 and for C2T2 in 2024. Reducing sugar content was lowest in C2T2; soil nitrate nitrogen accumulation was lowest in C3T2; soil available phosphorus was lowest in C1T3; and soil available potassium was lowest in CK. PFCE analysis indicated that C2T2 achieved multi-objective optimization for yield, quality, efficiency, and environmental sustainability.DiscussionBased on PFCE results and practical production considerations, applying biochar at 400–500°C pyrolysis temperature and 18–20 t ha−1 application rate is recommended for North China to maximize comprehensive benefits.